Sall1 transiently marks undifferentiated heart precursors and regulates their fate. (March 2016) - Morita, Yuika; Andersen, Peter; Hotta, Akitsu; Tsukahara, Yuko; Sasagawa, Noriko; Hayashida, Naoko; Koga, Chizuko; Nishikawa, Misato; Saga, Yumiko; Evans, Sylvia M.; Koshiba-Takeuchi, Kazuko; Nishinakamura, Ryuichi; et al.
Abstract: Cardiac progenitor cells (CPCs) are a crucial source of cells in cardiac development and regeneration. However, reported CPCs are heterogeneous, and no gene has been identified to transiently mark undifferentiated CPCs throughout heart development. Here we show that Spalt-like gene 1 ( Sall1 ), a zing-finger transcription factor, is expressed in undifferentiated CPCs giving rise to both left and right ventricles. Sall1 was transiently expressed in precardiac mesoderm contributing to the first heart field (left ventricle precursors) but not in the field itself. Similarly, Sall1 expression was maintained in the second heart field (outflow tract/right ventricle precursors) but not in cardiac cells. In vitro, high levels of Sall1 at mesodermal stages enhanced cardiomyogenesis, whereas its continued expression suppressed cardiac differentiation. Our study demonstrates that Sall1 marks CPCs in an undifferentiated state and regulates cardiac differentiation. These findings provide fundamental insights into CPC maintenance, which can be instrumental for CPC-based regenerative medicine. Highlights: Spalt-like1 (Sall1) marks cardiac progenitors in an undifferentiated state. Sall1 + cells give rise to four chambers of the developing heart. Sall1 positively regulates cardiac progenitor genes. Sall1 has a biphasic role during cardiomyogenesis in vitro.